Physical Therapist Management of Patients With Suspected or Confirmed Osteoporosis: A Clinical Practice Guideline From the Academy of Geriatric Physical Therapy. Issue 2 (11th April 2022) - Hartley, Gregory W.; Roach, Kathryn E.; Nithman, Robert W.; Betz, Sherri R.; Lindsey, Carleen; Fuchs, Robyn K.; Avin, Keith G.
Abstract : A clinical practice guideline on physical therapist management of patients with suspected or confirmed osteoporosis was developed by a volunteer guideline development group (GDG) that was appointed by the Academy of Geriatric Physical Therapy (APTA Geriatrics). The GDG consisted of an exercise physiologist and 6 physical therapists with clinical and methodological expertise. The guideline was based on a systematic review of existing clinical practice guidelines, followed by application of the ADAPTE methodological process described by Guidelines International Network for adapting guidelines for cultural and professional utility. The recommendations contained in this guideline are derived from the 2021 Scottish Intercollegiate Guideline Network (SIGN) document: Management of Osteoporosis and the Prevention of Fragility Fractures . These guidelines are intended to assist physical therapists practicing in the United States, and implementation in the context of the US health care system is discussed.